Cardiac Rhythm Device Contact Dermatitis. Issue 1 (13th August 2012) - Kang, Jaskaran; Simpson, Christopher S.; Campbell, Debra; Borici‐Mazi, Rozita; Redfearn, Damian P.; Michael, Kevin A.; Abdollah, Hoshiar; Baranchuk, Adrian
<x xml:space="preserve">Abstract</x> We present a series of three cases of patch testing confirmed cardiac rhythm device induced contact dermatitis. In the first two cases, there was complete resolution with device extraction and reimplantation with another device with either an absence of the offending agent or a coating with another resin or metal. These cases illustrate the difficulties in diagnosing pain, tenderness, and dermatological manifestations in patients with cardiac rhythm devices (pacemakers and implantable cardioverter defibrillators)